Transcatheter surgery of residual right ventricular outflow tract stenosis - K. A. Rzayeva; A. V. Gorbatykh; I. Yu. Zhuravleva; I. A. Soinov; A. V. Voitov; A. N. Arkhipov; Yu. Yu. Kulyabin; A. V. Bogachev-Prokofiev; Yu. N. Gorbatykh; A. M. Chernyavsky (Российский кардиологический журнал)
Over the past 40 years, various types of prostheses have been developed for right ventricular outflow tract reconstruction. However, conduit stenosis and insufficiency due to valve degeneration occur frequently, decreasing the lifetime of patients. Transcatheter stenting of conduits does not always give favorable results and can lead to severe pulmonary regurgitation. The novel method of percutaneous pulmonary valve implantation is a good alternative to the surgical intervention according to data on long-term survival and quality of life.